KREATIFITAS GURU FIQIH DALAM MENINGKATKAN KETERAMPILAN BELAJAR PESERTA DIDIK DI MADRASAH ALIYAH MA’ARIF 4 DARURRAHMAN MELARIS KECAMATAN MARGA TIGA TAHUN PELAJARAN 2022/2023 - Jamil (UNISAN JURNAL, 2024)
Fiqh teachers must be creative so that teaching and learning activities are not boring. Teacher creativity is also important in achieving student learning outcomes. This research aims to determine teacher creativity in an effort to increase student motivation when learning. A teacher of Fiqh subjects must be able to create a comfortable learning atmosphere by using varied learning methods and media so that students do not feel bored and will be more motivated to study the material presented so that the results obtained from the learning process are maximum and can later be achieved. apply it in everyday life. Effective teaching requires good planning. The media that will be used in the teaching process also requires good planning. This type of research aims to find an overview of teacher creativity Fiqh in improving students' learning skills. The research used a qualitative approach with the key informant being the Madrasah Aliyah Ma'arif 4 Darurrahman Melaris Fiqh teacher. Data was obtained from observations and interviews. When the data is collected, it is then analyzed using Miles et al's version of the theory, namely data reduction, data presentation, verification and drawing conclusions. Conclusions are drawn with inductive thinking. From the results of the research, the author can conclude that the creativity of the Fiqh teachers at Madrasah Aliyah Ma'arif 4 Darurrahman Melaris in teaching is considered to be very good. It is proven that the teachers in delivering the subject matter use various learning methods and use various learning media so that the delivery of the Fiqh subject matter can be achieved. presented in an interesting way and creates a pleasant atmosphere and eliminates students' learning boredom in class. The evaluations carried out by Fiqh teachers to see students' abilities when studying are very diverse, including written, oral, portfolio assessments, as well as practical assessments. With the creativity of the Jurisprudence Teacher at Madrasah Aliyah Ma'arif 4 Darurrahman Melaris, students' learning skills are increasin.